A morphological trait involved in reproductive isolation between Drosophila sister species is sensitive to temperature. Issue 12 (25th May 2021) - Peluffo, Alexandre E.; Hamdani, Mehdi; Vargas‐Valderrama, Alejandra; David, Jean R.; Mallard, François; Graner, François; Courtier‐Orgogozo, Virginie
Abstract: Male genitalia are usually extremely divergent between closely related species, but relatively constant within one species. Here we examine the effect of temperature on the shape of the ventral branches, a male genital structure involved in reproductive isolation, in the sister species Drosophila santomea and Drosophila yakuba . We designed a semi‐automatic measurement machine learning pipeline that can reliably identify curvatures and landmarks based on manually digitized contours of the ventral branches. With this method, we observed that temperature does not affect ventral branches in D. yakuba but that in D. santomea ventral branches tend to morph into a D. yakuba ‐like shape at lower temperature. We found that male genitalia structures involved in reproductive isolation can be relatively variable within one species and can resemble the shape of closely related species' genitalia through plasticity to temperature. Our results suggest that reproductive isolation mechanisms can be dependent on the environmental context. Abstract : The closely related species Drosophila yakuba and Drosophila santomea have distinctive ventral branches, a male genital structure involved in reproductive isolation. We designed a semi‐automatic method to measure the shape of the ventral branches and found that temperature does not affect ventral branches in D. yakuba but that in D. santomea ventral branches tend to morph into a D. yakuba ‐like shape at lower temperature. ​